IMPLEMENTATION OF CREATIVE TECHNOLOGY IN AGRICULTURE AND FISHERIES BASED ON ARTIFICIAL INTELLIGENCE TO INCREASE THE QUALITY AND SELLING VALUE OF A PRODUCT - Christian, Alexander Aldi; Nugraha, Mohammad Fauzan; Firdaus, Deva Densyah; Fauzana, Aldrian Daffa; Ramadhan, Muhamad Luqman; Wahyu, Ari Purno (CENTRAL ASIA AND THE CAUCASUS, 2022)
Improving the quality of a product is a must so that the value of the product has a high selling value, for example in the fields of agriculture and fisheries which are part of the support for the Indonesian economy, it becomes an important part so that the independence and economy of farmers and fishermen can be increased, because a result In agriculture and fisheries, a monitoring process needs to be carried out so that the resulting products are ready to be marketed and have a high value, at this time farmers and fishermen will carry out a sorting process on each agricultural product so that the value and conditions are in accordance with export standards and are at least suitable for export. sold and have high competitiveness with agricultural products from outside, in agriculture for example the sorting system will be done manually by sorting strawberries but this becomes a problem if the fruit is stored in large quantities so that the sorting process is missed, this is if it is the same in the field of fisheries and lobster breeding, for example, lobsters that have the same size and in accordance with export standards will have a high selling value, the process of applying sorting and monitoring of agricultural products at this time can use an image processing technique where the sorting process and monitoring can be done for 24 hours and the monitoring data can be used as an evaluation reference to analyze the next harvest.